2009
DOI: 10.1097/tp.0b013e318192897a
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variation in Inducible Costimulator Gene With Outcome of Kidney Transplantation

Abstract: The present results indicate that potentially functional genetic variation in T-cell costimulatory molecule ICOS has an effect on the outcome of kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 17 publications
1
49
2
Order By: Relevance
“…In the present study, we extended our investigation to subsequent ICOS gene polymorphisms which were recently described as functional ones [17,19] and were shown to be associated with susceptibility to multiple sclerosis [19] and outcome after renal [18] or hematopoietic stem cell transplantation [29], but not to melanoma [30]. [19], the frequency of the AA genotype was significantly lower in MS patients with relapsing-remitting disease than in controls, and those patients had a lower relapse rate and MS severity score.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the present study, we extended our investigation to subsequent ICOS gene polymorphisms which were recently described as functional ones [17,19] and were shown to be associated with susceptibility to multiple sclerosis [19] and outcome after renal [18] or hematopoietic stem cell transplantation [29], but not to melanoma [30]. [19], the frequency of the AA genotype was significantly lower in MS patients with relapsing-remitting disease than in controls, and those patients had a lower relapse rate and MS severity score.…”
Section: Discussionmentioning
confidence: 89%
“…The ICOSc.602A>C and ICOSc.1624C>T polymorphisms have been described as susceptibility markers of outcome after renal transplantation [18] and hematopoietic stem cell transplantation [29] Additionally, we included the ICOS ISV1+173T>C polymorphism in our study, which does not influence ICOS mRNA level in CD4 + cells but, since this polymorphism is located near the CTLA-4 gene, variations at that position influence CTLA-4 mRNA expression for both CTLA-4 isoforms, the soluble and full length (membrane) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association with outcome of kidney transplantation was reported in seven genetic studies (Slavcheva et al, 2001;Gendzekhadze et al, 2006;Wisniewski et al, 2006;Gorgi et al, 2006;Kusztal et al, 2007Kusztal et al, , 2010Kim et al, 2010). On the other hand, four studies did not succeed in replicating the association with CTLA4 (Dmitrienko et al, 2005;Haimila et al, 2009b;Krichen et al, 2009Krichen et al, , 2010. The SNP CTLA4+49 A/G (rs231775) is the most frequently studied variant and most often found to be associated.…”
Section: Co-stimulator Receptor Genes May Predispose To the Poor Outcmentioning
confidence: 99%
“…Two of the genetic variants of CD28 were included in three different association studies but no association was found (Haimila et al, 2009b;Krichen et al, 2009;Kusztal et al, 2010). CTLA4 gene polymorphisms have been examined in relation to kidney transplantation in a few studies (Table2).…”
Section: Co-stimulator Receptor Genes May Predispose To the Poor Outcmentioning
confidence: 99%